FORMING A HEALTHY LIFESTYLE FROM STUDENT BENCHES - Horoshko , O.; Zakharchuk , O.; Marchyshyn , S.; Kostyshyn , L.; Sakhatska , I.; Drachuk , V.; Ezhned , A.; Mykhailiuk , N.; Matushchak , M. (Collection of scientific papers «ΛΌГOΣ», 2022)
The article is devoted to the peculiarities of the formation of a healthy lifestyle among young people, the problem of improper food organization and ways to solve them at the level of a higher education institution. One of them is related to the lack of an adequate level of knowledge in nutrition, the main purpose of which is to form a conscious attitude of students to nutrition. and learning the skills of its correction. The appropriate skills will make it possible with your own mind not only to ensure a healthy way of life, but also to skillfully use them in practical activities. Despite the rapid progress in the social and medical spheres, the population of Ukraine, like the rest of the world, suffers from non-communicable diseases, which are getting younger over the years. The main indicators that characterize the state of health of society are not only the average life expectancy, but also the quality of life, since the incidence of endocrine diseases, metabolic disorders, a significant spread of diseases of the circulatory system, complications of diabetes has doubled over the last decade [1]. Its relevance does not decrease during the widespread spread of viral diseases, as a healthy lifestyle is one of the main components of immunity. One of the key aspects in the formation of negative trends in the field of public health, or the development of non-communicable diseases, is irrational nutrition, which leads to overweight, obesity, hypertensive disease, etc. [2]. To prevent non-communicable diseases and fight them, the WHO has developed a Global Strategy [3], which is based on a rational diet, a healthy lifestyle and physical activity. Constant violation of a healthy lifestyle and diet is characteristic of the younger generation, which is explained by a number of factors: indifferent attitude to one’s health, fast pace of life, overload, and sometimes lack of funds. All these factors, to a greater or lesser extent, are characteristic of student youth, who are the basis of the development of society, its energy component [4], therefore, teaching students about proper nutrition remains relevant.